2015
DOI: 10.1039/c5fo00295h
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary phytoestrogen intake and bone mineral density varied with estrogen receptor alpha gene polymorphisms in southern Chinese postmenopausal women

Abstract: the association of the dietary phytoestrogen intake and BMD in southern Chinese postmenopausal women varied with ERα gene polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Oral administration of ferutinin, a plant-derived ester of a sesquiterpenic alcohol, which acts as an ERα agonist (IC 50 = 33.1 nM) and an agonist/antagonist for ERβ (IC 50 = 180.5 nM), was able to improve bone regeneration of critical-size bone defects in vivo (Zavatti et al, 2015). Finally, a recent study revealed that in southern Chinese postmenopausal women the PhyEs dietary intake influences the bone mineral density, depending on the different ERα gene polymorfisms (Luo et al, 2015). …”
Section: Natural Xenoestrogensmentioning
confidence: 99%
“…Oral administration of ferutinin, a plant-derived ester of a sesquiterpenic alcohol, which acts as an ERα agonist (IC 50 = 33.1 nM) and an agonist/antagonist for ERβ (IC 50 = 180.5 nM), was able to improve bone regeneration of critical-size bone defects in vivo (Zavatti et al, 2015). Finally, a recent study revealed that in southern Chinese postmenopausal women the PhyEs dietary intake influences the bone mineral density, depending on the different ERα gene polymorfisms (Luo et al, 2015). …”
Section: Natural Xenoestrogensmentioning
confidence: 99%
“…Other validated dietary collection tools included dietary records or diary (n = 7, 15%) (42,44,62,68,90,150,158), 24-h or 48-h recalls (n = 6, 13%) (44,45,66,69,148,154), brief diet history questionnaire (n = 1, 2%) (94), and dietary history interviews (n = 1, 2%) (162). These methods were used to measure intakes of isoflavones (n = 19, 41%) (48,49,52,63,64,68,69,145,148,149,153,155,160,161,166,167,170,171,174), flavonoids (n = 13, 28%) (42, 46, 63, 114, 146, 147, 156, 162-165, 169, 172, 174, 175), lignans (n = 3, 7%) (147,154,173), phytoestrogens (both isoflavones and lignans) (n = 6, 13%) (45,66,150,151,157,175), and total (poly)phenols (n = 6, 13%) (44,62,…”
Section: Validation Of the Methodsmentioning
confidence: 99%
“…To determine the validity of the dietary assessment tool, 34 (74%) studies used other dietary assessment methods as references, including multiple (n = 7, 21%) (145,154,161,164,165,172,176) or single (n = 11, 32%) (42,44,62,68,94,150,154,155,161,166,170) measurement(s) of dietary records, multiple (n = 1, 3%) (171) or single (n = 4, 12%) (64,146,163,175) weighed food records, multiple 24-h (n = 9, 26%) (44,66,149,156,157,160,(167)(168)(169) or 48-h (n = 1, 3%) recalls (69), or other FFQs (n = 3, 9%) (50,158,168). Meanwhile, 17 (37%) studies compared dietary assessment methods against (poly)phenol biomarkers, from 24-h urine (n = 4, 24%) (45,52,69,170), spot urine (n = 6, 35%) (44,52,62,(148)(149)(150), fasting pla...…”
Section: Validation Of the Methodsmentioning
confidence: 99%
“…Phytoestrogens are nonsteroidal compounds that are chemically similar to animal estrogens and can directly or indirectly bind to estrogen receptors, exhibiting certain estrogenic or anti‐estrogenic effects. Phytoestrogens have been reported to have anti‐osteoporosis effects, and the effects were related to estrogen receptor alpha (Luo et al., 2015). Lignans such as enterodiol ( ED ) and enterolactone ( EL ) are one category of phytoestrogens, in addition to isoflavones such as genistein and daidzein, as well as coumarins such as coumestrol and wedelolactone (Luo et al., 2015; Tu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%